Implementation of Individual Reality Therapy to Address Sibling Rivalry in Children Aged 7-8 Years - Maharani, Laila; Monica, Mega Aria; Primanisa, Reiska; Purwanti, Sri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
By using reality counseling techniques and previous research findings on sibling rivalry, individual counseling reality techniques aim to identify sibling rivalry in early childhood. One form of sibling rivalry is sibling rivalry, where brothers and sisters compete for parental attention and affection. Each child has a different personality and needs. In this literature review, the concepts of counseling and reality theory are used to discuss sibling rivalry behaviors that occur in early childhood. WDEP is a stage of reality counseling where counselors help counselees describe what they want, their desired behavior, self-evaluate, and plan their desired behavior. This can help reduce brother-sister rivalry behavior in early childhood. This study applied a qualitative descriptive approach. with a literature review. The results of the literature review showed that reality counseling can reduce brother-sister rivalry behavior in early childhood.